Power, Rights, and Authority: The Qing Dynasty’s “Bengka Case” from a Legal Anthropological Perspective: Focusing on the Land System in the Tibetan Areas of Northwest Yunnan - YE, Yuanpiao (Journal of Research for Christianity in China (JRCC), 2025)
The Bengka Case occurred in the Nujiang Gorge along the Yunnan-Tibet border in the eighth year of the Xianfeng reign (1858). This anti-foreign religion movement, orchestrated by the Naxi chieftain, Tibetan Buddhist monasteries, and the Tibetan aristocracy, marked the first major setback for French Catholic missionaries in Tibet’s frontier regions. Regarding the causes of this incident, this paper employs historical archives and field materials to refute both the anti-imperialist patriotism theory and the religious conflict theory. It depicts the intrinsic connection between Christian propagation and land tenure systems, revealing the tangled web of power, rights, and authority pursued by different actors. The paper attributes the incident’s outbreak to conflicts arising from divergent understandings of land ownership between Tibetan folk customs and modern legal concepts, offering insights for academic reflection on the dialectical relationship between folklore and law.